The Role of Women in Improving the Family Economy in Saolat Village, South Wasile District, East Halmahera District, North Maluku Province - Tirsa Bahi; Femmy C. M. Tasik; Joanne V. Mangindaan (Journal La Bisecoman, 2024)
Every family is faced with various needs. Therefore, to be able to achieve needs, the role of all family members is needed. This research was conducted to determine the role of women in improving the family economy in Saolat Village, South Wasile District, East Halmahera Regency, North Maluku Province. The research was conducted using a qualitative design. Data was collected through interviews, observation and review of secondary data documents. The data analysis technique is carried out in the stages of data reduction, data presentation and drawing conclusions and verifying them. The research findings show that the role of women in improving the family economy in Saolat Village, South Wasile District, East Halmahera Regency, North Maluku Province, results from sufficient income and is very helpful in increasing the husband's income, the family economy becomes stable, education has a big influence on the world of work, social interactions become better.